البحث في قضايا الراهن وسلطة النموذج الغربي في تحليل الخطاب السردي نماذج لكتب مختارة - حفري, فطيمة الزهرة (University of Eloued جامعة الوادي, 2017)
ينشد هذا المقال البحث في قضايا الراهن وسلطة النموذج الغربي في عديد الكتب التي لطالما شكلت مرجعية نقدية و لا سيما تلك التي تأخذ بيد الباحث وتمكنه من شد معول التحليل وفق مقاربات البناء والدلالة خاصة تلك المبثوثة في ثنايا الخطاب السردي . إنّ الحديث عن ضبط آليات المنهج في الممارسة التطبيقية النقدية أصبح أكثر من ضرورة واستجابة لهذا الحديث تأتي هذه الدراسة ضوءا كاشفا ينضاف إلى سلسلة الإيضاحات، حيث أصبح الباحث يلمح شيوع النماذج الغربية في معظم الكتب المرجعية النقدية التي تؤكد على ضرورة التحلي؛ هي قضية تودي بطريقة ما بالباحث إلى مزالق العجلة في الفهم، والإبطاء في استيعاب عديد المناهج وعليه لزاما أن يضطلع الباحث على مفاهيم عربية تشعره بحقيقة ما يجري حوله، واستجابة لهذه المعطيات يفرز المقال عديد النماذج المختارة التي حاولت جاهدة تارة وجادة تارة أخرى استثمار النموذج الغربي في تحليل الخطاب السردي قاعدة له This article seeks to search in the current issues and the authority of the Western model in the many books that have long been critical of reference and especially those that take the researcher, however, and being able to pick strain analysis approaches in accordance with the construction and significance especially those broadcast in the folds of narrative discourse. Talking about adjusting the curriculum mechanisms in Applied critical practice has become more of a necessity and in response to this talk of this study come light revealing figures must be added to a series of clarifications, where he became a researcher hints prevalence of Western models in most books monetary reference which emphasizes the need to be; is the issue of claim somehow scholar to the pitfalls of the wheel in the understanding, and the delay in accommodating many curriculum and therefore obliged to undertake a researcher at the Arab concepts can feel what is going on around him, and in response to these facts secreted article several selected models that tried very hard at times and serious at other times invest the Western model in the analysis of narrative discourse his base.
Keywords: الخطاب السردي، النقد، اللغة; Narrative discourse, criticism, language.